2019
DOI: 10.1371/journal.pone.0212471
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and adiponectin dynamics at patients with rectal neoplasm - Gender differences

Abstract: Background Numerous studies associate adipokines with colorectal malignancy, but few data deal with patients suffering exclusively of rectal carcinoma (RC). Aims We evaluated leptin and adiponectin levels in RC patients compared to healthy population and their dynamics after surgery. Material and methods Serum leptin and adiponectin were evaluated before surgery in 59 RC consecutive patients (38 males and 21 females), and in age and weight ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…While our study is the first to investigate the impact of endometrial cancer treatment on adipocytokines and IGFs, previous research on different cancer types has shown varying fluctuations in response to surgical stress. For instance, Florescu et al noted decreased adiponectin levels 24 h after rectal carcinoma surgery, returning to baseline within 7 days [88]. They suggested that surgical stress triggers an adaptive inflammatory process affecting adiponectin levels [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our study is the first to investigate the impact of endometrial cancer treatment on adipocytokines and IGFs, previous research on different cancer types has shown varying fluctuations in response to surgical stress. For instance, Florescu et al noted decreased adiponectin levels 24 h after rectal carcinoma surgery, returning to baseline within 7 days [88]. They suggested that surgical stress triggers an adaptive inflammatory process affecting adiponectin levels [88].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Florescu et al noted decreased adiponectin levels 24 h after rectal carcinoma surgery, returning to baseline within 7 days [88]. They suggested that surgical stress triggers an adaptive inflammatory process affecting adiponectin levels [88]. Additionally, Shi et al indicated a potential role of adipose tissue in mitigating the stress response during surgery through adiponectin release [89].…”
Section: Discussionmentioning
confidence: 99%